2021
DOI: 10.1080/21623945.2021.1924957
|View full text |Cite
|
Sign up to set email alerts
|

The value of sex-specific abdominal visceral fat as measured via CT as a predictor of clear renal cell carcinoma T stage

Abstract: Although much is known about how adipose tissue affects the development of clear cell renal carcinoma (ccRCC), little information is available for the utility of sex-specific abdominal visceral fat composition as a predictor of clear cell renal carcinoma (ccRCC) T stage. We conducted CTbased sex-specific abdominal fat measurements in ccRCC patients to assess whether VFA distribution could predict the ccRCC T stage. In total, 253 patients (182 males and 71 females) from our hospital with pathologically confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We investigated continuous VAT and rVAT while several other studies used medians or proportions of VAT 10,14,15,[18][19][20] . Also, most studies were conducted in Asian populations [8][9][10][14][15][16][17][18][19][20] which have been reported to have higher TAT and VAT compared to our Dutch population 30 , implying that results may not be directly comparable.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…We investigated continuous VAT and rVAT while several other studies used medians or proportions of VAT 10,14,15,[18][19][20] . Also, most studies were conducted in Asian populations [8][9][10][14][15][16][17][18][19][20] which have been reported to have higher TAT and VAT compared to our Dutch population 30 , implying that results may not be directly comparable.…”
Section: Discussionmentioning
confidence: 68%
“…We also found no associations of adipose tissue parameters with stage II or III compared to stage I disease. In contrast, Guo et al reported in 253 Chinese patients with ccRCC that patients with high rVAT had increased risk of stage III-IV compared with stage I-II disease, and this relationship was similar for males and females 8 . In a Korean study with 706 localized stage I-II RCC the highest quartile of rVAT had the highest proportion of stage I disease.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations